PENGUSULAN DESAIN ANTARMUKA YANG ERGONOMIS UNTUK WEBSITE PRAKTIKUM PERANCANGAN DAN PENGENDALIAN PRODUKSI: Studi Kasus Universitas Pembangunan Nasional Veteran Jakarta - Ainun Halivia (2023)
Production Planning and Inventory Control Practicum is one of the mandatory practicums at the Industrial Engineering Study Program at the Universitas Pembangunan Nasional Veteran Jakarta which studies the basic concepts of Production Planning and Inventory Control. In carrying out comfortable practicum activities, appropriate modern learning facilities are needed to make it easier for students to carry out practicum according to user needs. Therefore, the purpose of this study is to provide interface design proposals according to user needs and to analyze the results of the design of the Ergonomic Design and Production Planning and Inventory Control Practicum website based on the level of usability and legibility. This research is based on ergonomic principles with the Human Centered Design (HCD) approach, Eye-tracking and QUIS questionnaires. Based on the level of importance of the design elements, typography is the most needed according to user needs so the researchers made 6 design suggestions by differentiating the selection of typography in the design. Based on user level, the selected design is Design 6 satisfaction in terms of user satisfaction assessment in screen appearance and overall appearance. The user satisfaction level is 8.79 and has the highest satisfaction level on 18 criteria. Then in usability testing, obtaining a design efficiency and effectiveness level of 100% and a usability score of 83 and getting the title b. With these results, design 6 is in the excellent category, which means the application is satisfactory and can be used as a recommend design. In the legibility test, it was found that 7% of the respondents experienced eye fatigue and 93% of the respondents entered the normal blink rate. Thus, design 6 is said to be ergonomic because it has a low level of eye fatigue.